Surface-air energy exchange over eastern Venezuela as related to streamflow and cumulonimbus cloud systems - Renné, David S., author; Colorado State University, Department of Atmospheric Science, publisher (Colorado State University. Libraries, 1970)
Solar and net radiation measurements made during the Venezuelan International Meteorological-Hydrological Experiment (VIM-HEX) conducted in Venezuela in the summer of 1969 are discussed, and the results presented in two separate parts of this paper. In the first part it is shown that the average net radiation surplus observed at the ground is converted to sensible and latent heat transfer to the atmosphere. The sensible heat transfer can be computed directly from morning and afternoon clear-day temperature soundings. It is shown that the ratio of sensible to latent heat transfer over eastern Venezuela during the study period is about 0.63. Based on the total energy balance at the earth's surface, and dense rain-gauge measurements made over the study area, a stream runoff of 0.07 cm/day per unit area is computed. This compares quite well with the observed runoff per unit area of 0.09 cm/day. It is concluded that single station meteorological measurements coupled with areal rainfall data can give a first approximation to the hydrology of a small tropical region over the time period of a month or so. In the second part of this report the radiation data is nondimensionalized by comparison with a standard, and the values are located with respect to the center of an associated mesosystem photographed by the VIM-HEX radar facility. The radius of the observed radiation parameter from the center of the mesosystem is also non-dimensional zed. In this reference system it is observed that there is a sharp decrease in solar radiation and net radiation within the mesosystem boundaries, and a rapid increase outside the boundaries. It is concluded that the direct supply of energy from the ground decreases toward the center of a tropical disturbance over land and may vanish completely. In this respect the land-based tropical cumulonimbus differs significantly from oceanic mesosystems, where the supply of sensible and latent energy from the water actually increases toward the center with very little diurnal control.
CER70-71DSR22.
September 1970.
This report was prepared under contract no. N00014-68-0493-0002 between the Office of Naval Research and Colorado State University.
Keywords: Earth temperature; Cumulonimbus; Streamflow